The ‘Five Million Hectare Reforestation Program’ in Vietnam: an analysis of its implementation and transaction costs: a case study in Hoa Binh province - Huong, T.T.T.; Zeller, M.; Hoanh, Chu Thai (2014)
This research study uses a qualitative approach to examine the implementation of the ‘Five Million Hectare Reforestation Program’ (the 5MHRP) in Vietnam, and to explore the underlying reasons for local people’s participation in the program. The study also uses a transactional model to examine the private transaction costs borne by farmers when carrying out forest management activities under the program. The study reveals that: (i) the implementation of the program was generally characterized by a top-down process, (ii) the principal contribution to household benefits derived from forest management activities was the collection and sale of non-timber forest products, not the subsidy provided by the government, (iii) the main challenges faced during implementation of the program were the low and fixed subsidies provided, the improper types of trees being planted, poor access to the forest, and a lack of awareness among local people towards the benefits to be derived from participation in the forest management program, and that (iv) under the program’s community contracts, attending meetings (52%) and self-monitoring activities (35%) constituted the largest proportion of total time spent on forest management, while under the individual contracts, self-monitoring activities (98%) were the main component. Participating in the planting and protection of forests under the program brought greater benefits to households than when involved in forest protection activities alone. The main implications of this study are that an increase of payments under both types of contract, and especially the community contract, as well as the provision of higher quality seedlings and fertilizers, need to be taken into consideration in future initiatives. In addition, local communities and authorities should be further empowered, and their contribution should be taken into consideration in future programs.